La première formation de paysagistes concepteurs en France, ruptures et continuités - Bernadette Blanchon (Projets de Paysage)
In this article we look back on the principal teaching approaches adopted at the Section du paysage et de l'art des jardins (Department of Landscape Architecture and Garden Arts) which was created in 1945 at the École nationale d’horticulture (National School of Horticulture) to dispense the first training courses for landscape architects in France. Using testimonies and archives, we review the changes and progress made by the department during three main periods. After a brief review of the reasons for its creation and of the people who were instrumental in establishing it, the description of the first period (1946-1961) focuses on architects and urban planners from the École des Beaux-Arts who taught the French tradition of garden design. During the second period (1961-1971), young graduates started teaching and developed further the curriculum. In the third period (1971-1974) the teachers left the Department to join a new short-lived organisation, the Centre national d'étude et de recherche du paysage CNERP (National Centre for Research in Landscape Architecture) (1972-1979), while new contributors recentred workshops and field trips on an approach that was more architectural before the department was finally closed down. Thanks to contributions from abroad and from other disciplines, the orientation of the teaching alternated between engineering and creativity, the legacy of which may be called into question today.